2012
DOI: 10.1515/bmc-2012-0025
|View full text |Cite
|
Sign up to set email alerts
|

Milk lipid secretion: recent biomolecular aspects

Abstract: Neonates of most species depend on milk lipids for calories, fat-soluble vitamins, and bioactive lipid components for growth and development during the postnatal period. To meet neonatal nutrition and development needs, the mammary gland has evolved efficient mechanisms for synthesizing and secreting large quantities of lipid during lactation. Although the biochemical steps involved in milk lipid synthesis are understood, the identities of the genes mediating these steps and the molecular physiology of milk li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 111 publications
2
31
0
1
Order By: Relevance
“…). All milk protein and half of the total fatty acids in bovine milk are synthesized within the mammary epithelial cells (Mcmanaman ), and milk protein and lipid biosynthesis are regulated at many levels within the BMEC. In our data, about 95 proteins related to lipid metabolism were identified with COG categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). All milk protein and half of the total fatty acids in bovine milk are synthesized within the mammary epithelial cells (Mcmanaman ), and milk protein and lipid biosynthesis are regulated at many levels within the BMEC. In our data, about 95 proteins related to lipid metabolism were identified with COG categories.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the biochemical pathways in mammary glands related to biosynthesis and secretion of lipids and proteins are regulated by complex gene networks (Bionaz & Loor 2008;Liu et al 2013). All milk protein and half of the total fatty acids in bovine milk are synthesized within the mammary epithelial cells (Mcmanaman 2012), and milk protein and lipid biosynthesis are regulated at many levels within the BMEC. In our data, about 95 proteins related to lipid metabolism were identified with COG categories.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it was observed that oxytocininduced myoepithelial cell contraction is required to release mature LDs from secretory cells into luminal spaces ( Figure 1D; Masedunskas et al, 2017). This suggests that LD droplet secretion is intermittently stimulated by milk let-down (Masedunskas et al, 2017), and is not a continuous process as previously assumed from static observations (Mather and Keenan, 1998;Neville, 2009;McManaman, 2012). Intriguingly, alveolar cells switch their cellular function from LD secretion to uptake during mammary gland involution, triggering a complex program of cell death that returns the mammary gland to a near pre-pregnant state (Kreuzaler et al, 2011;Sargeant et al, 2014).…”
Section: Multidimensional Imaging Of the Lactating Mammary Glandmentioning
confidence: 50%
“…Lipids, particularly triacylglycerols, are major milk constituents (Oftedal, 1984) that are packaged and secreted in the form of membrane-coated lipid droplets (LDs) during lactation (Walther et al, 2017). While classical biochemical and morphological analyses have revealed valuable insights into LD assembly, fusion and secretion, the kinetics underlying this dynamic process remained unclear (Mather and Keenan, 1998;McManaman, 2012).…”
Section: Multidimensional Imaging Of the Lactating Mammary Glandmentioning
confidence: 99%
“…1) [13], and en masse transport of phospholipids, along with triglycerides and cholesterol esters, to the apical plasma membrane in association with milk lipid secretion (pathway 1, Fig. 1) [15]. …”
Section: Introductionmentioning
confidence: 99%